Cologne Consensus Conference 2016: assessment in accredited CME/CPD, 16 and 17 September 2016, Cologne, Germany. Issue 1 (1st January 2017) - Murray, Ron
ABSTRACT: Participants and faculty members from around Europe and North America met in Cologne Germany on 16 and 17 September 2016, for the fifth annual Cologne Consensus Conference under the auspices of the European Cardiology Section Foundation (ECSF) in cooperation with various European and North American professional medical associations, accrediting bodies and CME providers. The conference was preceded by an afternoon workshop, organised by the European Board for Accreditation in Cardiology (EBAC) that allowed participants to observe a range of current e-learning modules in CME and to discuss implications for the accreditation of micro-e-learning. The conference theme was Assessment and the first day's presentations covered Assessment Methods, Needs Assessment, Assessment of Interprofessional Teams, and Assessment of Providers. The second day's topics were Assessment of Knowledge, Assessment of Practical Skills, Evaluation methods and the link between Assessment and Licensure. A diverse range of professional expertise among participants from both sides of the Atlantic provided stimulating discussion to make the conference a rewarding experience for all concerned.